“Life Goes On” – everyday life of children with Down syndrome and their families – selected aspects. - Lipińska-Lokś, Jolanta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The birth of a child is a major event in family life, which makes parents take on an important role in their lives, characterised by new tasks, chief among which are the care and upbringing of their offspring. Unfortunately, in many families, some factors emerge that may affect their functioning, disrupt the course of family life, and leave a permanent mark on the family’s history. Such a situation can be difficult for many –and many parents find the process of accepting a child with a disability (Down syndrome) and themselves as parents of a child with Down syndrome a long and arduous journey, since taking care of a child, upbringing and supporting their development is an issue in itself, but also a challenge for parents. In many cases, both the child and their parents need support in their daily life, ensuring their high quality of life. The objective of this study is to outline the functioning of families of children with Down syndrome. Due to the complex nature of the issue at hand, only selected aspects of the functioning of families were diagnosed, showcasing the changes in the family life and its functioning as a result of the birth of children with Down syndrome. The study was based on qualitative methodologies, by analysing individual cases using interview technique and interview dispositions. The research group comprised 10 families of children with intellectual disabilities, and the interviewed group was made up of 10 mothers and 3 fathers in Zielona Góra.